2021
DOI: 10.1002/adfm.202101058
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter‐Size All‐inorganic Perovskite Crystalline Thin Film Grown by Chemical Vapor Deposition

Abstract: The chemical vapor deposition (CVD) method is a dry approach that can produce high quality crystals and thin films at large scale which can be easily adapted by industry. In this work, CVD technology is employed to grow high quality, large size all‐inorganic cesium lead bromide perovskite crystalline film for the first time. The obtained films have millimeter size crystalline domains with high phase purity. The growth kinetics are examined in detail by optical microscopy and X‐ray diffraction. The deposition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…However, the PL peak shifted from ≈520 to ≈518 nm, corresponding to a reduced Stokes shift from 46.8 to 37.6 meV, which indicates an enlarged grain size and improved crystallinity and is in agreement with the XRD spectra analysis. [ 30 ] The rise in full width at half maximum (FWHM) from 16.8 to 20.9 nm may be attributed to the increase of inhomogeneous size distribution as well as the density of states near the band edge. [ 31 ] The time‐resolved PL (TRPL) spectra of these films contain single exponential decay curves at low pump densities (<50 nJ cm −2 ) with time constants of 1.6 and 2.0 ns (Figure S3a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…However, the PL peak shifted from ≈520 to ≈518 nm, corresponding to a reduced Stokes shift from 46.8 to 37.6 meV, which indicates an enlarged grain size and improved crystallinity and is in agreement with the XRD spectra analysis. [ 30 ] The rise in full width at half maximum (FWHM) from 16.8 to 20.9 nm may be attributed to the increase of inhomogeneous size distribution as well as the density of states near the band edge. [ 31 ] The time‐resolved PL (TRPL) spectra of these films contain single exponential decay curves at low pump densities (<50 nJ cm −2 ) with time constants of 1.6 and 2.0 ns (Figure S3a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, thin films of lead-free materials were also successfully deposited via one-step CVD at ambient atmosphere or controlled pressure. , The novelty in the deposition process of MA 3 Bi 2 I 9 is the showerhead-based deposition tool for perovskites, which offered precise control options and paved the way for large-area production (Figure b) . Recently, it was first demonstrated that one-step CVD could also be utilized to deposit millimeter-size CsPbBr 3 crystalline thin films with high phase purity, showing a promising preparation method suitable for PV applications (Figure c, d) …”
Section: One-step Cvdmentioning
confidence: 99%
“…(d) Line-cut extracted from GIWAXS map (red) and simulated X-ray diffraction pattern (black) of orthorhombic phase CsPbBr 3 . Reproduced with permission from ref . Copyright 2021 Wiley–VCH.…”
Section: One-step Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] Nie's team obtained a millimeter‐scale orthorhombic phase CsPbBr 3 film with high‐crystallinity by vapor‐phase deposition, and they fabricated a lateral diode, significant photo‐generated voltages and short‐circuit currents were observed, indicating that the as‐growth CsPbBr 3 films had high crystallinity and admirable photoelectric properties. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%